2019
DOI: 10.1371/journal.pone.0221027
|View full text |Cite
|
Sign up to set email alerts
|

Spatial clustering of notified tuberculosis in Ethiopia: A nationwide study

Abstract: Background Tuberculosis (TB) remains a major health problem worldwide and in Ethiopia. This study aimed to investigate the spatial distributions of notified TB over the whole territory of Ethiopia and to quantify the role of health care access, environmental, socio-demographic, and behavioural factors associated with the clustering of TB. Methods A spatial analysis was conducted using national TB data reported between June 2016 and June 2017 in Ethiopia. Spatial cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 18 publications
5
27
0
Order By: Relevance
“…The spatial heterogeneity in the prevalence of TB among people living with HIV was significantly associated with underlying variability in area-level socio-economic variables such as low wealth index, low adult literacy rate, and close distance to the international border. The observed association between the prevalence of TB and socio-economic factors has already been described in the existing literature [2527]. A high prevalence of TB has previously been reported among people with low wealth quintile and low educational status in several countries such as South Africa [28], Kenya [29], China [30], and Brazil [31].…”
Section: Discussionmentioning
confidence: 77%
“…The spatial heterogeneity in the prevalence of TB among people living with HIV was significantly associated with underlying variability in area-level socio-economic variables such as low wealth index, low adult literacy rate, and close distance to the international border. The observed association between the prevalence of TB and socio-economic factors has already been described in the existing literature [2527]. A high prevalence of TB has previously been reported among people with low wealth quintile and low educational status in several countries such as South Africa [28], Kenya [29], China [30], and Brazil [31].…”
Section: Discussionmentioning
confidence: 77%
“…However, studies from Africa and Ethiopia using TB notification data aggregated at larger areas and populations, to assess the spatial distribution of the disease have poor resolution. Moreover, several of the previous studies conducted at broader geographic level did not exclude cases who came from neighbouring areas diagnosed and treated in the reporting health facilities and could have underestimated or overestimated the true disease burden [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Research findings from different parts of Ethiopia [ 2 6 ] showed the presence of high TB burdens with varied magnitude across its regions and woredas (third level administrative hierarchy in Ethiopia). Recent studies that used the applications of geographic information system (GIS) in the analysis of TB data exhibited that TB incidence and prevalence in Ethiopia have spatial and space-time variations [ 7 11 ].…”
Section: Introductionmentioning
confidence: 99%